Clinical Values of Preoperative Use of Antibiotics in Transanal Endoscopic Microsurgery. (2nd November 2018) - Chen, Jingbo; Li, Yupeng; Xi, Xiangpeng; Qiao, Lili; Yang, Mingyu; Xia, Lijian; Zhou, Yanbing
ABSTRACT: Objective. To investigate the clinical values of preoperative use of antibiotics in transanal endoscopic microsurgery (TEM). Methods: Thirty patients undergoing TEM surgery to treat rectal neoplasms in our hospital were selected in this study. All patients were randomly divided into two groups: antibiotic group that antibiotics were used before and after surgery, and control group that antibiotics were only used after surgery. Several markers were evaluated before and after surgery in all patients, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), changes procalcitonin (PCT), white blood cell count (WBC), neutrophils (NE%) and temperature (T). Results: The patients in the antibiotic group at the first and third days after surgery showed lower values of ESR, CRP, WBC, NE% and T than the control group ( p < 0.05), furthermore, the WBC and NE% were significantly decreased at the third day after surgery compared with the first day after surgery. For the PCT, there was a significant difference in the first day after surgery between the two groups ( p < 0.05), but no significant difference was observed between them at the third day after surgery ( p > 0.05). Conclusion: The preoperative use of antibiotics in TEM surgery to treat rectal neoplasms may become an effective method to reduce inflammation and prevent infecting after surgery, which will be verified by an amount of studies on large sample.